The New Public Management and the Public Sector Performance - Peter, Idoko (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
The proliferation of reforms in public administration based on the principles and instruments of the New Public Management (NPM) have triggered protest from and collective action by many professional groups in various sectors (healthcare, education, justice, social work, research.) and raised questions about the future of professionals working in the public service, particularly as concerns their autonomy. This exploratory study indicates that public administration in the 21st century is undergoing dramatic change, especially in advanced economies, but also in many parts of the developing world such as Nigeria. Globalization and the pluralization of service provision are the driving forces behind these changes. Policy problems faced by governments are increasingly complex, wicked and global, rather than simple, linear, and national in focus. And yet the prevailing paradigms through which public sector reform are designed and implemented are relatively static and do not fully encompass the significance or implications of these wider changes. While public sector reforms in the developing world such as Nigeria are influenced by policy experiments and organizational practices originating in OECD countries, they tend to operate within the traditional public administration paradigm. Consequently, there is often a discrepancy between the thrust of public sector reform efforts in developing country contexts and wider shifts in the nature of governance and contemporary approaches to public management grounded in OECD experience. It was concluded therefore that Nigeria has embraced the concept of new public management from their western originator but its core principles and tenets are not strictly applied in the management of public sector administration. It was recommended among others that for us to achieve the tenets of new public management in Nigeria, the government need to be honest, transparent, probity and accountability in the political leadership management including the managers in the public sector organizations.